Effects of Adipose-tissue Derived Mesenchymal Stem Cells on PBMCs in Co-culture with HeLa Cell Line - Maryam Dorfaki; mahdi ghatrehsamani; fahimeh Lavi Arab; Mona Roozbehani; Majid Khoshmirsafa; Reza Falak; Fatemeh Keshavarz; Fatemeh Faraji (Turkish Journal of Immunology)
Objective: Cervical cancer, the most common reproductive system cancer being women, is the fourth leading cause of cancer-related deaths. The use of mesenchymal stem cells (MSCs) for treating various diseases is being studied, but their use in cervical cancer has not been well explored. In this study we study investigated the effect of adipose tissue-derived MSCs on the apoptosis and proliferation of peripheral blood mononuclear cells (PBMCs) in co-culture with the HeLa cell line. MSCs were isolated from adipose tissue and then co-cultured with PBMCs, and HeLa cells at different time points (24, 48, and 72 hours). Materials and Methods: The effect of MSC cells on proliferation, apoptosis, and gene expression of the cytokines tumor necrosis factor alpha (TNF-α), transforming growth factor beta (TGF-β), interleukin (IL)-4, IL-2, and interferon-γ in PBMCs cultured together with HeLa cells was investigated using flow cytometry and real-time polymerase chain reaction (PCR), respectively. Results: Flow cytometry showed that co-culture of PBMCs/MSCs/HeLa significantly increased the proliferation of PBMCs at different time points, with a p-value of 0.0022. In addition, MSCs significantly decreased apoptosis of PBMCs in co-culture with HeLa at 48 h. the p-value was 0.0022. Real-time PCR showed that the expression of TGF-β in PBMCs/MSCs/HeLa co-culture increased after 24 h, with a p-value of 0.006. Conclusion: These data showed that adipose-derived MSCs can stimulate the proliferation and survival of PBMCs and enhance the apoptosis of HeLa cells, indicating their potential as immunomodulatory therapy for cervical cancer cells. However, further research is required to fully understand the underlying mechanisms and optimize therapeutic approaches involving PBMCs and MSCs.